Unpacking "ownership" in development co-operation effectiveness: Perspectives of Southern recipients - Debapriya Bhattacharya; Towfiqul Islam Khan; Najeeba Mohammed Altaf (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
Country ownership' continues to grow more as an idealized requirement than an operational concept for effective development co-operation. Provider countries often shy away from taking onboard recipient countries' development priorities, public financial management and procurement systems, results frameworks, and monitoring mechanisms. Based on the outputs of a research programme, this paper reviews the experience of six countries from three continents regarding the application of the concept of 'ownership' at the sectoral level in the respective countries. The paper explores what 'collective ownership' instead of 'country ownership' would entail-from conceptualization to delivery of a foreign aid-supported development intervention. The findings are pertinent to the ongoing debates concerning the relevance and application of 'development effectiveness' principles for achieving effective and sustainable development outcomes and the scope for replicability of good practices within a specific national context.
Keywords: 330; collective ownership; effective development co-operation; sector